Synthesis of polyozellin, a prolyl oligopeptidase inhibitor, and its structural revision. Issue 5 (1st March 2018) - Takahashi, Shunya; Kawano, Takahiro; Nakajima, Natsumi; Suda, Yasuaki; Usukhbayar, Narandulam; Kimura, Ken-ichi; Koshino, Hiroyuki
Graphical abstract: Abstract: Polyozellin is a p -terphenyl compound which was isolated from Polyozellus multiplex, and exhibits an inhibitory activity against prolyl oligopeptidase (POP). Its structure was assigned as1 having a p -terphenyl skeleton including a p -substituted dibenzofuran moiety by spectroscopic analyses and chemical means. This paper describes the total syntheses of the proposed structure1 for polyozellin and its o -isomer2, revising the structure of polyozellin to the latter. These syntheses involved a double Suzuki-Miyaura coupling using chlorophenylboronic acid as a common key building block, and Cu mediated Ullmann cyclization as key steps. The inhibitory activities of synthetic compounds against POP and cancer cells were also evaluated.